Expert Consensus on Active Health Management of Short Stature Based on the Integration of Sports, Healthcare and Education(2025 Edition) - China Behavioral Medical Research Center for Growth and Development, Behavioral Medicine Branch of Chinese Medical Association Committee on Growth, Development and Metabolism, China Maternal and Child Health Research Association (Xiehe Yixue Zazhi)
Short stature is a disease that affects children's physical and psychological health, closely associated with lifestyle factors such as diet, physical activity, and sleep. Under the framework of integrated sports, healthcare, and education, the active health management model seeks to consolidate resources and expertise from sports, medicine, and education to provide comprehensive, systematic guidance for child health strategies. This expert consensus focuses on active health management for short stature, addressing key aspects including growth monitoring, nutrition, exercise, sleep, and psychological well-being, while also considering comorbidities associated with short stature. By engaging families, schools, communities, and healthcare institutions in a multi-setting approach, it aims to deliver evidence-based, practical guidance for effective management of short stature.